Higher education and SDG17 : partnerships for the goals - Cabrera, Ángel; Cutright, Drew (Higher education and the sustainable development goals, 2023)
Co-edited by the president of Georgia Tech, one of America's leading research universities, Higher Education and SDG17: Partnerships for the Goals demonstrates how higher education institutions are uniquely positioned to act as catalysts, conveners, and supporters of key partnerships to help advance the United Nations' Sustainable Development Goals. Featuring authors from higher education institutions, educational networks, and governing bodies around the globe, chapters provide case studies, inspiration, reflections, and critical perspectives from a variety of geographies, disciplines, and partners on how HEI partnerships can rapidly accelerate progress on the goals. Responding to an urgent need for a mind shift towards collaboration and collective action, this is a uniquely global roadmap for higher education leaders, students, faculty, staff, and other partners, to take on the immense challenge of achieving the Sustainable Development Goals. Higher Education and the Sustainable Development Goals is a series of 17 books that address each of the SDGs in turn specifically through the lens of higher education. Adopting a solutions-based approach, each book focuses on how higher education is advancing delivery of sustainable development and the United Nations global goals. The series is edited by Wendy Purcell, Professor with Rutgers University and Academic Research Scholar with Harvard University; Emeritus Professor and University President Emerita.